MEDIATING AFFECT OF ORGANIZATIONAL COMMITMENT ON THE RELATIONSHIP BETWEEN ADMINISTRATORS’ TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL SUPPORTED AND TEACHERS’ JOB PERFORMANCE AT THE COMMUNICATION UNIVERSITY OF SHANXI, SHANXI PROVINCE - Tao, Yin; Tipanark, Peerapong; Muangman, Pornthep (วารสารวิจัยธรรมศึกษา, 2024)
The objectives of this research were: (1) To propose of the mediating effect of organizational commitment on the relationship between administrators’ transformational leadership, perceived organizational supported, and teachers’ job performance at the Communication University of Shanxi when the model fit with the empirical data.; and (2) To investigate the factors has direct and indirect effect of organizational commitment on the relationship between administrator’s transformational leadership, perceived organizational supported, and teachers’ job performance at the Communication University of Shanxi. The research was a mixed methodology, including qualitative and quantitative research.The population of the research consisted of 683 who were administrators, staff and full-time teachers of communication university of Shanxi. A proportional stratified random sampling method was used to sample, totaling 363 persons.The instruments used for data collection were a five-level rating scale questionnaire. The statistics used for data analysis were descriptive statistics and Confirmative Factor Analysis. The research findings revealed that:The research findings revealed that:(1)Structural Equation Modeling (SEM.) the mediating effect of organizational commitment on the relationship between admistrators’ transformational leadership, perceived organizational supported, and teachers’ job performance at the Communication University of Shanxi fit with the empirical data.(2).Administrators’ transformation leadership and perceived organizational supported has a significant direct effect on teachers’ job performance.(3). Administrators’ transformation leadership and perceived organizational supported has a significant indirect effect on teachers’ job performance (TJP) through the teachers’ organizational commitment.